Prevalence of Ciprofloxacin and Nalidixic Acid Resistant Salmonella enterica serovar Typhi in Bangladesh - Afroj, Shirin; Ilias, Mohammad; Islam, Maksuda; Saha, Samir K (Bangladesh Journal of Microbiology, 2012)
A total of 1,059 Salmonella enterica serovar Typhi were isolated from blood samples during January 2006 to October 2007 from urban rural facilities in Dhaka, Bangladesh, of which 980 (92.5%) isolates were nalidixic acid resistant. The minimum inhibitory concentrations (MIC) of ciprofloxacin (CIP) were determined for 127 nalidixic acid resistant Salmonella enterica serovar Typhi (NARST) strains (every fifth) isolated during 2006. Nine isolates were found to be resistant against CIP (3%) with high MIC (12 - >32 ?g/mL). Only four isolates were found to be sensitive (MIC <0.125 ?g/mL), whereas most of the isolates (N=113) showed reduced susceptibility (MIC 0.125 2 ?g/mL) to CIP. All these isolates were subjected to molecular typing by multiplex PCR on VNTR (variable number tandem repeats) loci, which revealed eight different VNTR patterns. Almost all CIP resistant strains had similar genetic organization, identical to the most common VNTR type. Restriction fragment length polymorphism (RFLP) analysis of the gyrA gene revealed point mutations at Ser-83 and Asp- 87 in all CIP resistant strains. DOI: http://dx.doi.org/10.3329/bjm.v28i1.11802 Bangladesh J Microbiol, Volume 28, Number 1, June 2011, pp 7-11